Non-contact Health Detection Device based on Millimeter Wave Radar - Ding, Zequn; Wang, Tianhu; Xia, Huijun; Wang , Jungang; Liu, Yihan; Yu, Tailiang (Scientific Journal of Technology, 2026)
With the deepening implementation of the "Healthy China 2030" strategy, health issues have increasingly garnered widespread attention. Understanding one's health status primarily involves monitoring the normality of basic physiological parameters. For instance, conditions such as fever or pneumonia may manifest as an elevated heart rate and more rapid, deepened breathing. Timely acquisition of basic human physiological information has thus become a critical requirement in the modern medical industry. To address these challenges, this project proposes designing a non-contact health detection system leveraging STM32 and millimeter-wave technology. The millimeter-wave radar is employed to capture micro-motion signals generated by chest movements during breathing and heartbeat. STM32 serves as the core processing unit to analyze the collected data. An OLED display then presents real-time information, including heart rate, respiratory rate, and human body distance. Simultaneously, this data is transmitted to mobile devices via WiFi or Bluetooth modules. On smartphones, phase signal-based charts of heart rate and respiratory rate are generated, enabling intuitive visualization of current health metrics. Furthermore, the highly integrated nature of its modules significantly reduces the system's size, allowing broader access to basic human physiological information with greater convenience for a wider population.